A strategic knowledge map for the research and development department in a manufacturing company - Małgorzata Śliwa; Justyna Patalas-Maliszewska (Foundations of Management, 2016)
Knowledge is a corporate resource, being grounds for initiating activities, which is important in a dynamic economy. The difficulties related to obtaining tacit knowledge, related primarily to experience and observation of the knowledge employee (Mendryk, 2011), encourage the companies to use tools supporting knowledge management and location. This article attempts at designing a dedicated, strategic knowledge map for a research and development department in a manufacturing company. Based on the reference works, the detailed characteristics of specific sources of knowledge in a manufacturing company and tools supporting the process of converting the tacit knowledge into explicit one, for example, the knowledge maps, were devised. Then, a strategic knowledge map model was designed for the research and development department (hereinafter abbreviated as SKM - R&D) in the manufacturing company, comprising the following components: (1) fields of knowledge, (2) internal and external processes in the R&D department, and (3) sources of knowledge. Then, a practical implementation of the SKM - R&D model was presented.
Keywords: 650; knowledge map; tacit knowledge; explicit knowledge; research and development department; manufacturing company